Advances in genomic diagnosis of a large cohort of Egyptian patients with disorders of sex development. Issue 6 (19th March 2021) - Mazen, Inas; Mekkawy, Mona; Kamel, Alaa; Essawi, Mona; Hassan, Heba; Abdel‐Hamid, Mohamed; Amr, Khalda; Soliman, Hala; El‐Ruby, Mona; Torky, Ahmed; El Gammal, Mona; Elaidy, Aya; et al.
Abstract: Disorders/differences of sex development (DSD) comprise a group of congenital disorders that affect the genitourinary tract and usually involve the endocrine and reproductive system. The aim of this work was to identify genetic variants responsible for disorders of human urogenital development in a cohort of Egyptian patients. This three‐year study included 225 patients with various DSD forms, referred to the genetic DSD and endocrinology clinic, National Research Centre, Egypt. The patients underwent thorough clinical examination, hormonal and imaging studies, detailed cytogenetic and fluorescence in situ hybridization analysis, and molecular sequencing of genes known to commonly cause DSD including AR, SRD5A2, 17BHSD3, NR5A1, SRY, and WT1 . Whole exome sequencing (WES) was carried out for 18 selected patients. The study revealed a high rate of sex chromosomal DSD (33%) with a wide array of cytogenetic abnormalities. Sanger sequencing identified pathogenic variants in 33.7% of 46, XY patients, while the detection rate of WES reached 66.7%. Our patients showed a different mutational profile compared with that reported in other populations with a predominance of heritable DSD causes. WES identified rare and novel pathogenic variants in NR5A1, WT1, HHAT, CYP19A1, AMH, AMHR2, and FANCA and in the X‐linked genes ARX and KDM6A . In addition, digenic inheritance was observed in two of our patients and was suggested to be a cause of the phenotypic variability observed in DSD.